A level-1 pixel based track trigger for the CMS HL-LHC upgrade - Moon, Chang-Seong [UNESP] (My University, 2016)
We present feasibility studies to investigate the performance and interest of a Level-1 trigger based on pixels. The Level-1 (real-time) pixel based tracking trigger is a novel trigger system that is based on real-time track reconstruction algorithms able to cope with very high rates and high flux of data in a very harsh environment. The pixel detector has an especially crucial role in precisely identifying the primary vertex of rare physics events from the large pile-up of events. The goal of adding the pixel information already at the real-time level of the selection is to help reducing the total Level-1 trigger rate while keeping a high selection capability. This is quite an innovative and challenging objective for the upgrade of the experiments for the High Luminosity LHC.